2015
DOI: 10.1002/jcc.23965
|View full text |Cite
|
Sign up to set email alerts
|

The role of induced current density in Steroelectronic effects: Perlin effect

Abstract: The normal and reverse Perlin effect is usually explained by the redistribution of electron density produced by hyperconjugative mechanisms, which increases the electron population within axial or equatorial proton in normal or reverse effect, respectively. Here an alternative explanation for the Perlin effect is presented on the basis of the topology of the induced current density, which directly determines the nuclear magnetic shielding. Current densities around the C-H bond critical point and intra-atomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Hernández‐Lima et al used J (1) ( r ) and its atomic partition to understand the Perlin effect in cyclic organic molecules, Figure . The Perlin effect is the differing behavior of geminal hydrogen atoms with regard to their chemical shift, where δ ax < δ eq ( δ ax > δ eq for the reverse Perlin effect), where δ ax and δ eq are the axial and equatorial chemical shifts, respectively.…”
Section: Applications Of Qtaimmentioning
confidence: 99%
See 1 more Smart Citation
“…Hernández‐Lima et al used J (1) ( r ) and its atomic partition to understand the Perlin effect in cyclic organic molecules, Figure . The Perlin effect is the differing behavior of geminal hydrogen atoms with regard to their chemical shift, where δ ax < δ eq ( δ ax > δ eq for the reverse Perlin effect), where δ ax and δ eq are the axial and equatorial chemical shifts, respectively.…”
Section: Applications Of Qtaimmentioning
confidence: 99%
“…Induced current density by a magnetic field in the H ax –C–H eq plane and perpendicular to the C–H ax (A, C) and C–H eq of cyclohexane (A, B) and 1,3‐dithiane (C, D) bonds …”
Section: Applications Of Qtaimmentioning
confidence: 99%
“…The magnetically induced current density ( J ( r )) is the quantum mechanical observable that is directly connected to these electronic flows. Studying the topology of J ( r ) is important to understand NMR chemical shifts or the magnetic susceptibility of a molecule . It can also be used to study the electron delocalization in bonds and molecules .…”
Section: Introductionmentioning
confidence: 99%
“…The strength and tropicity of J ( r ) are also useful to explain the shielding constants of nuclei close to a specific circulation. The chemical shift of nuclei above or below a paratropic/diatropic current would be shifted downfield (deshielded)/upfield (shielded) in an NMR spectrum, respectively …”
Section: Introductionmentioning
confidence: 99%
“…For example, in a previous study we showed that for a series of cyclohexanes in which 1,3 positions were interchanged by a heteroatom and present Perlin effect, there are at least two directions of B that correlate with the observed trends. Both B directions are necessary to explain the chemical shifts . Another example is fullerenes, in which the electron delocalization occurs in a three‐dimensional space.…”
Section: Introductionmentioning
confidence: 99%